Transcervical Foley’s catheter: a promising option for induction of labour - Pandey, Divya; Salhan, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We hereby report the results of a small randomized prospective study where we compared the efficiency and efficacy of transcervical extra-amniotic Foley catheter placement to intravaginal dinoprostone gel as a method of induction of labour.